The Handling and Sampling of Radical Cystectomy Specimens: A Standardized Approach for Pathological Evaluation - Francesca Sanguedolce; Angelo Cormio; Magda Zanelli; Maurizio Zizzo; Andrea Palicelli; Alessandra Filosa; Ugo Giovanni Falagario; Andrea Benedetto Galosi; Luigi Cormio; Giuseppe Carrieri; Roberta Mazzucchelli (Methods and Protocols)
An accurate histopathological evaluation of radical cystectomy (RC) specimens is crucial for optimal tumor staging, prognosis, and therapeutic decision making. The increasing demand for precision medicine and multidisciplinary oncological management emphasizes the necessity for standardized protocols in the handling and sampling of bladder cancer specimens. The effective processing of RC specimens begins with the integration of clinical and anamnestic data, along with appropriate formalin fixation methods to meet diagnostic needs. The pathologist must meticulously document the macroscopic characteristics and dimensions of the surgical specimen, especially in post-neoadjuvant chemotherapy (post-NAC) cases where the primary tumor may not be macroscopically visible. Sampling strategies should ensure a comprehensive assessment of the primary tumor and any extra-organ or metastatic involvement. Despite international guidelines, variability in pathology practices persists, particularly concerning prostate sampling in RC and the use of frozen sections for margin assessment. Addressing these challenges necessitates a consensus-driven, standardized approach to improve the reproducibility and quality of histopathological data. By addressing gaps in current pathology practices, this review advocates for uniform protocols that enhance diagnostic accuracy, ultimately improving patient care and clinical decision making.